Forecasting analytics for industry 4 - Alroomi, Azzam (Edelweiss Applied Science and Technology, 2024)
This research through a systematic review highlights studies that have delved into analytics for Industry 4.0 with the aim of discussing and reflecting on the manner in which applications of Artificial Intelligence such as Machine Learning and Deep Learning have helped in forecasting and facilitated informed decision-making.